Third Millennium B.C. Interregional Exchange in Southwest Asia with Special Reference to the Keban Region of Turkey - Yener, Aslıhan (1980)
Ph.D. Dissertation; Order No. 8028817; cf. DissAbstr 41/07 (January 1981) 3167-A.